2010
DOI: 10.1016/j.dr.2010.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The development of attention to simple and complex visual stimuli in infants: Behavioral and psychophysiological measures

Abstract: The study of visual attention in infants has used presentation of single simple stimuli, multidimensional stimuli, and complex dynamic video presentations. There are both continuities and discontinuities in the findings on attention and attentiveness to stimulus complexity. A continuity is a pattern of looking that is found in the early part of infancy that remains throughout adulthood. A discontinuity is an emerging sensitivity to the content of the information in the stimulus presentations and alterations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
96
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 29 publications
5
96
0
Order By: Relevance
“…We found greater P1 ERP amplitude and increased current density amplitude around the P1 peak latency in brain regions involved in early visual processing (Martinez et al, 1999; Richards, 2005) during sustained attention than inattention. Sustained attention is hypothesized to increase general arousal (Reynolds & Richards, 2007; Richards, 2009, 2010) and information processing efficiency (Reynolds et al, 2010; Richards, 2010; Richards et al, 2010). The current finding of enhanced brain activity to visual targets during sustained attention is consistent with the hypothesis that sustained attention enhances brain alertness, which in turn facilitates infant information processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found greater P1 ERP amplitude and increased current density amplitude around the P1 peak latency in brain regions involved in early visual processing (Martinez et al, 1999; Richards, 2005) during sustained attention than inattention. Sustained attention is hypothesized to increase general arousal (Reynolds & Richards, 2007; Richards, 2009, 2010) and information processing efficiency (Reynolds et al, 2010; Richards, 2010; Richards et al, 2010). The current finding of enhanced brain activity to visual targets during sustained attention is consistent with the hypothesis that sustained attention enhances brain alertness, which in turn facilitates infant information processing.…”
Section: Discussionmentioning
confidence: 99%
“…Infant sustained attention plays an important role in infant cognitive processes, such as stimulus orienting, information processing, and recognition memory (see Colombo, 2001; Richards, 2009, 2010 for reviews). Infant sustained attention has been well defined by infant HR changes derived from electrocardiogram (ECG) recordings (Reynolds & Richards, 2007).…”
mentioning
confidence: 99%
“…Richards, 2010) there has been a lack of data considering the dynamic processes of arousal and its moment-to-moment effects on cognition. Instead, the majority of data collected has averaged over these dynamic processes in order to obtain "more pure" or "cleaner" cognitive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Infants may engage in sustained attention for only 2–3 s, or not at all, when presented with simple stimuli, but may spend 20 s or more in sustained attention when the visual presentation is complex and dynamic (Reynolds & Richards, 2008; Richards, 2010; Richards & Casey, 1992). For example, Courage et al (2006) observed longer durations of sustained attention in response to complex stimuli (e.g., faces, Sesame Street) compared with achromatic patterns.…”
mentioning
confidence: 99%